A document analysis of drowning prevention education resources in the United States. Issue 1 (2nd January 2018) - Katchmarchi, Adam Bradley; Taliaferro, Andrea R.; Kipfer, Hannah Joy
ABSTRACT: There have been long-standing calls to better educate the public at large on risks of drowning; yet limited evaluation has taken place on current resources in circulation. The purpose of this qualitative research is to develop an understanding of the content in currently circulated drowning prevention resources in the United States. Data points ( n = 451) consisting of specific content within 25 different drowning prevention educational resources were analyzed using document analysis methods; a grounded theory approach was employed to allow for categorical development and indexing of the data. Results revealed six emerging categories, including safety precautions ( n = 152), supervision ( n = 109), preventing access ( n = 57), safety equipment ( n = 46), emergency procedures ( n = 46), and aquatic education ( n = 41). Results provide an initial insight into the composition of drowning prevention resources in the United States and provide a foundation for future research.